AN ASSESSMENT ON CONFLICT MANAGEMENT STRATEGIES IN ORGANIZATIONAL PERFORMANCE: A CASE STUDY OF A SELECTED MANUFACTURING COMPANY IN ABUJA, NIGERIA - Oriko, Sylvanus Ekonesie; Dankogi, Muhammed Ismaila; Ogbaini, Aliu Clement (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2024)
This study examines the impact of conflict management strategies on the attainment of organizational goals in selected manufacturing companies in Abuja. The study adopted a descriptive research design with two research questions raised and two research hypotheses. The study investigates conflict management strategies in nine manufacturing companies in Abuja, including 7up Bottling, Coca-Cola, Nigerian Breweries, Glasco Plastic Company, Ero Table Water, Alpha Ceramics and Aslo Glass. The research aims to establish the relationship between management strategies and organizational goal attainment. The study has limitations, such as its focus on a few selected firms and the small sample size, which may limit the generalizability of the findings. Data were generated through the use of a validated structured questionnaire. Descriptive and inferential statistics were employed to analyze data collected from the respondents. The study used Spearman correlation analysis as a methodology tool. The results showed a significant positive relationship between conflict management strategies (collective bargaining, compromise, and accommodation) and organizational goal attainment. Non-integrative strategies (competition, domination and avoidance) had a negative effect. Collective bargaining strategy had the highest positive correlation with goal attainment. The study recommends an inclusive and collaborative conflict management strategy, involving unions in strategic decisions, to avoid conflict insurrection. Conflict is unavoidable in organizations and can affect goal attainment depending on the chosen conflict management strategies.